2014
DOI: 10.1103/physreve.89.042105
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in partitioning systems with few degrees of freedom

Abstract: We study the behavior of a moving wall in contact with a particle gas and subjected to an external force. We compare the fluctuations of the system observed in the microcanonical and canonical ensembles, by varying the number of particles. Static and dynamic correlations signal significant differences between the two ensembles. Furthermore, velocity-velocity correlations of the moving wall present a complex two-time relaxation that cannot be reproduced by a standard Langevin-like description. Quite remarkably,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 28 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…(1a) and the original eq. A1 in [10] don't have the same last term. Such discrepancy is due to a confirmed misprint [1] in [10].…”
Section: Introductionmentioning
confidence: 99%
“…(1a) and the original eq. A1 in [10] don't have the same last term. Such discrepancy is due to a confirmed misprint [1] in [10].…”
Section: Introductionmentioning
confidence: 99%
“…The stochastic part is obtained by adding the Gaussian noise terms with amplitudes determined by imposing that the variances of the variables coincide with those computed within the canonical ensemble [17]. This yields …”
Section: ~ ~ M + X J Dv (M + ~ V)ft{mentioning
confidence: 99%
“…The effective force acting on the piston due to the collisions with gas particles, appearing in Equation (20), is given by two contributions, F coll = F L coll + F R coll . By taking into account the elastic collisions rule, Equation (1), these terms can be computed as follows:…”
Section: Piston Positionmentioning
confidence: 99%
“…The system at its ends interacts with thermal baths at fixed temperatures. It is easy to realize the analogy between such a generalized piston model and the systems of masses and springs: the pistons and the gas compartments play the role of masses and springs, respectively.Our model is an example of partitioning system (as the adiabatic piston), where previous studies showed that the presence of mobile walls can induce interesting behaviours [12][13][14][15][16][17][18][19][20][21]. Basically, in the study of partitioning systems, one can adopt two approaches: in terms of a Boltzmann equation [14] or introducing effective equations (Langevin-like) for suitable observables derivedà la Smoluchowski, i.e., from an analysis of the collisions particles/walls.…”
mentioning
confidence: 99%